A new strategy for integrating semiconducting SWCNTs into pseudo-cubic In2O3 heterostructures for solid-state symmetric supercapacitors with a superior stability and specific-capacitance. Issue 31 (24th July 2018) - Mishra, Rajneesh Kumar; Ryu, Jae Hyeon; Kwon, Hyuck-In; Jin, Sung Hun
Abstract : We report a one-step hydrothermal synthesis of semiconducting single-walled carbon nanotubes/pseudocubic In2 O3 heterostructures and successfully demonstrate LED lighting by using symmetric solid-state supercapacitors. Abstract : Herein, we report a rapid one-step hydrothermal synthesis of semiconducting single-walled carbon nanotubes/pseudo-cubic In2 O3 heterostructures (s-S/IHs) and successfully demonstrate LED lighting by using symmetric solid-state supercapacitors (SSCs). This is a simple, scalable, proficient and in situ synthesis method to harvest materials that can be engaged as cutting-edge electrode materials for high-energy SSCs. The cost effective and environment-friendly s-S/IH conveys excellent electrochemical properties with a high specific capacitance (641.1 F g −1 at a current density of 1.8 A g −1 ) and tremendous rate capabilities with an excellent capacitance (335.1 F g −1 at a current density of 3.8 A g −1 ). The SSC devices with a maximum potential window of 1.2 V are fabricated by using two similar s-S/IH electrodes in order to justify the outstanding performance for real-life energy storage devices. Notably, the SSC devices offered a high specific capacitance (139.5 F g −1 at 2 A g −1 ), a high energy density (6.9 W h kg −1 at 234.3 W kg −1 ), an ultra-high power density (789.3 W kg −1 at 4.6 W h kg −1 ), and a remarkable cycling stability (91.8% specific capacitance retention rate after 5000 cycles). These extraordinary findings illustrate an insight into designing a nanocube In2 O3 lattice deformed by very small concentration of semiconducting single-walled carbon nanotubes that are economically affordable and environmentally harmonious for the fabrication and demonstration of high performance SSC devices.